Social Protection of the Population of PostSoviet Armenia - Yarmaloyan, Marine (Journal of Sociology: Bulletin of Yerevan University, 2016)
Due to the dynamism of social and economic development, occurring changes and challenges of modernization it is impossible to definitively solve the problem of social insecurity. However, the statistical data and the results of sociological studies show that positive trends are achievable and effective measures of social protection (social, economic, legal, and political) promote to reduce social tension in society. The essence of social protection is not only to ensure the political, social and economic rights of citizens but also in the psychological component of personality. It is necessary to neutralize the sources of insecurity, which have a downward effect on the level and quality of life, namely to create high-paying jobs; improve the social security and social assistance, to effectively fight against corruption and crime, to improve social and economic stability.
Keywords: social protection, objective and subjective indicators of social protection, subjective wellbeing